Palladium-Catalyzed Selective Carbonylation Reactions of Ortho-Phenylene Dihalides with Bifunctional N,O-Nucleophiles - Fanni Bede; Attila Takács; László Kollár; Péter Pongrácz (Molecules)
Palladium-catalyzed carbonylation reactions of ortho-phenylene dihalides were studied using aminoethanols as heterobifunctional N,O-nucleophiles. The activity of aryl-iodide and -bromide as well as the chemoselective transformation of amine and hydroxyl functionalities were studied systematically under carbonylation conditions. Aminocarbonylation can be selectively realized under optimized conditions, enabling the formation of amide alcohols, and the challenging alkoxycarbonylation can also be proved feasible, enabling amide-ester production. Intramolecular double carbonylation reaction can be achieved using 1,2-diiodobenzene and amino alcohols featuring secondary amine groups, giving oxazocine derivatives. Useful reaction scope with various amino alcohols was performed with good isolated yields of the targeted compounds. Intramolecular C-O coupling of amide alcohols possessing bromo substituent in adjacent ortho position is also demonstrated as a potential next step in benzoxazepine heterocycle formation.